EFEKTIFITAS PEMBELAJARAN KOOPERATIF TIPE NHT DENGAN PENDEKATAN KONTEKSTUAL PADA PEMBELAJARAN BANGUN RUANG SISI DATAR - Lingga Nico Pradana (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
The purpose of this research was to determine the effect of learning models to student achievement. Learning models compared between NHT-CTL, NHT and direct instruction. Method of research used quasi experimental with the factorial design of 3x1. Population of this research was all students class VIII in SMP Negeri at Madiun City. The sampling technique using a stratified cluster random sampling. Samples in this research were 266 students with 91 students as experimental class I, 88 students as experimental class II and 87 students as control class. Data collection methods used documentation and test.Hypothesis testing was performed using one-way analysis of variance with unequal cells. Based on the results of hypothesis testwere concluded that NHT-CTL learning model gave better achievement than NHT learning model and direct instruction, while NHT learning model and direct instruction gave the same achievement.